THE DIVERSITY-ORIENTED SYNTHESIS OF SATURATED N-HETEROCYCLIC SCAFFOLDS BY POST-AZA-ANNULATION MODIFICATIONS - Bekbolatova, Ainara (School of Sciences and Humanities, 2023)
The synthesis of N-heterocyclic scaffolds that resemble biologically active molecules in an environmentally friendly, atom-efficient, cheap, and easily manageable way is among the main tasks for synthetic chemists. The diversity-oriented synthesis of heterocyclic scaffolds facilitated by multicomponent reactions constitute a powerful tool for the implementation of the above goal. In this research, the series of fused saturated N-heterocyclic compounds were synthesized through the post-aza-annulation modifications and characterized. The synthetic approach started with the condensation of readily available acetylacetone and a primary amine into corresponding enaminones. This was followed by the aza-annulation with maleic anhydride producing heterocyclic molecule featuring the carboxylic acid and keto-carbonyl functionalities. This molecule underwent subsequent heterogeneous reduction to remove the unsaturation. Finally, the resulting heterocyclic ketoacid was subjected in the Ugi multicomponent reaction with amine and isocyanide to yield the complex heterocyclic scaffolds in 21-50% overall yield. In total, nine fused heterocyclic products were obtained by varying the amine and isocyanide substrates in a highly diastereoselective fashion.
Keywords: saturated n-heterocyclic scaffolds; post-aza-annulation modifications